Diagnostic performance of 18F‐FDG‐PET/CT in inflammation of unknown origin: A clinical series of 317 patients. (24th January 2022) - Holubar, Jan; Broner, Jonathan; Arnaud, Erik; Hallé, Olivier; Mura, Thibault; Chambert, Benjamin; Sotto, Albert; Roubille, Camille; Gaujoux‐Viala, Cecile; Goulabchand, Radjiv
Abstract: Background: Inflammation of unknown origin (IUO) is a challenging situation in internal medicine. Objectives: To describe the final diagnoses in IUO and assess the helpfulness of 18 F‐fluorodesoxyglucose positron emission tomography with computerized tomography ( 18 F‐FDG‐PET/CT) in the diagnosis strategy. Results: A total of 317 IUO patients with 18 F‐FDG‐PET/CT were enrolled. A diagnosis was reached in 228 patients: noninfectious inflammatory diseases (NIID) (37.5%), infectious diseases (18.6%), malignancies (7.9%), and non‐systemic‐inflammatory miscellaneous diseases (7.9%). The two leading causes of NIID were polymyalgia rheumatica and giant cell arteritis. 18 F‐FDG‐PET/CT results were classified as true positive in 49.8% of patients and contributory in 75.1% of overall IUO patients (after the complete investigation set and a prolonged follow‐up). In multivariate analysis, only C‐reactive protein minimum level (≥50 mg/L) was associated with the contributory status of 18 F‐FDG‐PET/CT. Conclusion: Within the wide spectrum of IUO underlying diseases, 18 F‐FDG‐PET/CT is helpful to make a diagnosis and to eliminate inflammatory diseases. Obese patients constitute a specific group needing further studies.